KEKUATAN HUKUM TIDAK TERTULIS SEBAGAI SUMBER HUKUM WAD’I DI INDONESIA - Muhammad Jufri (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
The rule of law is well written or not, but the way this law will be the one deciding which set the course of a life. Life goes on in the community can not be released without the law because the law itself inevitably participate in order to help smooth the activities of a life lived in community. Indonesian law is a rule or norm in Indonesia. Contained in Indonesian law and apply it, as well as the enactment of this law is based on a particular time referred to as positive law (Ius Constitutum). In addition, positive law is divided into two types, namely the written and unwritten laws.